Effect of Foot Hidrotheraphy (Soak Feet Warm Water) Against Blood Pressure in Hypertensive Patients: A Literature Review - Ismail, Ismail (Poltekkes Kemenkes Gorontalo, 2024)
Background: Hypertension is a medical condition characterized by a continuous increase in blood pressure in the body's arteries. Purpose: This study aims to analyze the effect of foot hydrotheraphy ( warm water foot soak) on blood pressure in hypertensive patients with a literature review approachMethods: The author uses a literature review approach in compiling this paper, which involves exploring the 2018-2023 literature from national and international sources accessed through Google Scholar and Pubmed, which discusses the application of Foot Hydrotherapy as a method to reduce blood pressure.Results: The results showed a significant decrease in systolic (SBP) and diastolic (DBP) blood pressure after the application of hydrotherapy in patients with hypertension, with a decrease in SBP reaching 14.09 mmHg and DBP by 9.51 mmHg, while in pregnant women there was a decrease in SBP by 17.71 mmHg and DBP by 10.85 mmHg. Elderly people with hypertension also experienced a decrease in SBP by 14.04 mmHg and DBP by 9.03 mmHg after hydrotherapy. The temperature of hydrotherapy in hypertensive pregnant women is 40o-43oC to lower blood pressure, while temperatures of 37o-39oC are used to achieve a relaxing effect.Conclusion: Warm water hydrotherapy is considered an effective method in the management of blood pressure in various groups of hypertensive patients.